Curriculum Accommodation Implementation for Students with Special Needs in Kindergarten Inclusive Education - Martalenny, Elyza; Azizah, Nur (Journal of Innovation and Research in Primary Education, 2025)
Curriculum accommodation represents a critical component of inclusive education implementation for students with special needs, yet limited research examines these practices in early childhood settings within developing country contexts. This study investigated curriculum accommodation implementation across four key components in kindergarten inclusive education settings. A qualitative descriptive study was conducted across five kindergarten institutions implementing inclusive education in North Sangatta District, East Kutai Regency, Indonesia. Data were collected through unstructured interviews with ten participants comprising school principals and classroom teachers, supplemented by observation and document analysis. The interactive model of Miles and Huberman was employed for data analysis, with source triangulation ensuring validity. Analysis revealed substantial compliance with national guidelines across curriculum accommodation components. Of 28 accommodation indicators examined, 21 (75%) achieved full implementation compliance. Learning objectives accommodation demonstrated complete implementation across six indicators, including curriculum adoption, adaptation procedures, and competency standards integration. Content and material accommodations showed strong implementation in adaptation and relevance indicators, though systematic assessment procedures revealed partial compliance. Learning process accommodations achieved 92% compliance rate, with successful implementation of activity design, lesson planning, and collaborative teaching practices. Evaluation accommodations demonstrated 75% compliance, with effective adaptation of assessment methods while systematic curriculum development models showed partial implementation across all components. The findings demonstrate successful basic accommodation implementation while identifying gaps in systematic approaches requiring enhanced professional development and institutional support. Results provide evidence for inclusive education feasibility in early childhood settings when supported by appropriate policy frameworks, contributing valuable insights for scaling inclusive education initiatives in developing country contexts.